Defining next-generation additive manufacturing applications for the Ministry of Defence (MoD) - Busachi, Alessandro; Erkoyuncu, John Ahmet; Colegrove, Paul A.; Drake, Richard; Watts, Chris; Martina, Filomeno (Elsevier, 2016)
“Additive Manufacturing” (AM) is an emerging, highly promising and disruptive technology which is catching the attention of the Defence sector due to the versatility it is offering. Through the combination of design freedom, technology compactness and high deposition rates, technology stakeholders can potentially exploit rapid, delocalized and flexible production. Having the capability to produce highly tailored, fully dense, potentially optimized products, on demand and next to the point of use makes this emerging and immature technology a game changer in the “Defence Support Service” (DS2) sector. Furthermore, if the technology is exploited for the Royal Navy, featured with extended and disrupted supply chains, the benefits are very promising. While most of the AM research and efforts are focusing on the manufacturing/process and design opportunities/topology optimization, this paper aims to provide a creative but educated and validated forecast on what AM can do for the Royal Navy in the future. This paper aims to define the most promising next generation Additive Manufacturing applications for the Royal Navy in the 2025 – 2035 decade. A multidisciplinary methodology has been developed to structure this exploratory applied research study. Moreover, different experts of the UK Defence Value Chain have been involved for primary research and for verification/validation purposes. While major concerns have been raised on process/product qualification and current AM capabilities, the results show that there is a strong confidence on the disruptive potential of AM to be applied in front-end of DS2 systems to support “Complex Engineering Systems” in the future. While this paper provides only next-generation AM applications for RN, substantial conceptual development work has to be carried out to define an AM based system which is able to, firstly satisfy the “spares demands” of a platform and secondly is able to perform in critical environments such as at sea.
Keywords: Additive Manufactruing; Manufacturing Systems; Defence